Analysis of the Financial Performance of the Mekar Sari Village Government, Kumpeh Jambi District 2020-2022 - Berlin Dhamos Syahputra Silalahi; Wiwik Tiswiyanti; Susfa Yetti (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to analyze financial conditions by assessing the financial performance of the Mekar Sari Village Government, Kumpeh District. The data used in this research is secondary data sourced from the Mekar Sari Village Government Budget Realization report for the period 2020 to 2022. The ratio analysis used in this research is: 1) Effectiveness Ratio, 2) Efficiency Ratio, 3) Village Financial Independence Ratio, 4) Economic Ratio. The research results show that the performance of the Mekar Sari Village Government, Kumpeh District in 2020-2022 has an average effectiveness ratio of 92.12% with effective criteria. The average efficiency ratio is 98.47% with efficient criteria. The average village independence ratio is 107.50% with independent criteria. The economic ratio has a value of 98.52% with economic criteria